Dvoyetochiye [Colon]: A Historical-Linguistic Study - A. V. Ivanov (Научный диалог)
This paper systematically compiles information about the term dvoyetochiye [colon] and its equivalents, drawn from grammatical and lexicographical sources spanning the 16th to the early 19th centuries. Employing methods of comparative, semantic, and historical-linguistic analysis, it establishes that the word dvoyetochiye [colon] has held a terminological status since its first recorded mention in textual sources in 1619. The study reveals that from the early 17th century to 1810, the colon as a punctuation and diacritical mark served a range of functions, each corresponding to a distinct meaning of the term. Among these meanings are the following: a linear punctuation mark represented by two vertical dots; a sign indicating the end of a phrase; a superscript mark above the letter i; a superscript mark above ї; a superscript mark above ё; and a superscript mark denoting the distinct phonetic realization of adjacent vowels. The investigation identifies several doublet terminological designations, including dve tochki [two dots] (1738 — vertical colon / 1780 — horizontal colon), dvoesrochie (16th century), dvoestrochie (1640), dvosrochnaya (17th century), dva punkta [two points] (1627), diaeresis (1788), trema (1798), punkt dvoyakiy [double point] (1730), and dva apostrofa [two apostrophes] (1808). These designations are encapsulated within the terminological microfield of “Colon”, reflecting the dual representation of the corresponding sign in writing: horizontal (as a diacritical or pseudo-diacritical mark above a letter) and vertical (as a punctuation mark).